Perfomansi Sistem Solid Dry Pad Dengan Media Pendingin 50% Massa Dry Ice - Mahardika, I M. Arya; Wijaksana, Hendra; Suarnadwipa, Suarnadwipa (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract Refrigeration has the main function of cooling. Refrigeration is also a method of conditioning the room temperature to keep it below the ambient temperature. The use of Air Conditioning causes the level of global warming to be higher. Therefore, an energy efficient and environmentally friendly cooling system is needed, namely an evaporative cooling system. The use of Dry Ice as a dew point evaporative cooling pad has excellent evaporation properties. Dry ice is very useful for freezing and maintaining freezing because its very cold temperature is: -78.5oC or -109.3°F. In this study, a pad containing 50% dry ice was used with the research variable is the variation of air flow velocity V1=4,8m/s, V2=9,5m/s, V3=11,3m/s. Measurements were carried out covering aspects of decreasing dry bulb temperature, cooling, cooling effectiveness, and EER. The results obtained in this study, the decrease in dry bulb temperature tends to be large at air flow velocity of 4.8 m/s. The difference in the temperature of Tin and Tout 4.450C compared to the air flow velocity of 11.3 m/s, there is a decrease in the temperature of Tin and Tout 1.090C. Keywords: Evaporative Cooling, Dew Point, Dry Ice